Rekayasa Ulang Proses Bisnis (Business Process Reengineering) Prosedur Permohonan Surat Izin Cuti Karyawan untuk Peningkatan Efisiensi Waktu di Divisi Spun Yarns PT Indorama Synthetics Tbk - Yogi Agustian; Dedy Setyo Oetomo; Asep Hermawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The Employee Leave Request procedure at the Personnel Department, Spun Yarns Division, PT Indorama Synthetics Tbk, is still manual and paper-based, causing long waiting times and low efficiency. This study maps the current (As Is) process, identifies the most dominant Non-Value Added (NVA) components, and formulates and analyzes a To Be proposal through Business Process Reengineering (BPR) with its gap analysis. This applied, quantitative-descriptive study uses flowcharts and time observation to classify Value-Added (VA) and NVA activities. Results show the As Is process has 9 steps with a total cycle time of 194.00 minutes, of which 153.2 minutes (79.0%) are NVA, mainly waiting time for HOD/Supervisor approval (72.5 minutes) and Remuneration Staff processing (49.8 minutes). The To Be design reduces actors from five to four, eliminates 4 steps, digitizes 2 steps, and automates 2 steps. The gap analysis shows the cycle time cut to 45.80 minutes, a 76.39% efficiency gain.